2002
DOI: 10.1557/jmr.2002.0104
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic apatite formation on poly(lactic acid) composites containing calcium carbonates

Abstract: Poly(lactic acid) composites containing a mixture of calcium carbonates (vaterite, aragonite, and calcite) were prepared by a carbonation process in methanol. Soaking of the composites for 3 h in simulated body fluid (SBF) at 37°C resulted in the deposition of bonelike apatite particles on the composite surface. After soaking the composites, vaterite phase in the composites was forward to dissolve rapidly, resulting in increase the supersaturation of the apatite in SBF. 13 C cross-polarization magic angle spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…Formation of bonelike apatite layer on the surface of the artificial material is thus required for its ability to bond with the living bone without intervention of the fibrous tissue when it is used as a bone repairing material. 3 On this basis, extensive research has been explored on formation of bonelike apatite on various bioactive materials including NaOH and heat treated titanium and tantalum metals 4,5 and organic polymers [6][7][8] by means of biomimetic approach. This method consists of soaking bioactive materials in a simulated body fluid, SBF, with ion concentrations nearly equal to those of human blood plasma at physiological pH and temperature and analyzing the evolution of apatite formation with time.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of bonelike apatite layer on the surface of the artificial material is thus required for its ability to bond with the living bone without intervention of the fibrous tissue when it is used as a bone repairing material. 3 On this basis, extensive research has been explored on formation of bonelike apatite on various bioactive materials including NaOH and heat treated titanium and tantalum metals 4,5 and organic polymers [6][7][8] by means of biomimetic approach. This method consists of soaking bioactive materials in a simulated body fluid, SBF, with ion concentrations nearly equal to those of human blood plasma at physiological pH and temperature and analyzing the evolution of apatite formation with time.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at approximately 170 ppm are related to the carboxy groups. It has been reported that when a bivalent ion is coordinated with a carboxy groups, a new peak corresponding to that groups appears at the side of low magnetic field in the band 17) , and that, on the composites prepared from PLA and vaterite, a peak indicating the coordination between Ca 2+ ions originating from vaterite and the carboxy groups originating from PLA appears at approximately 172 ppm 18) . In this work, to identify the existence of the peak at approximately 172 ppm, each broad peak at approximately 170 ppm was deconvoluted into two peaks by using a 2-component Gaussian fitting method.…”
Section: Characterization Of Siv-pla(m) and Siv-pla(k) Fabricsmentioning
confidence: 99%
“…To eliminate this risk, it has been reported that the composites were fabricated using the polymer sponge coated with bioactive materials such as hydroxyapatite or Bioglass. [7][8][9] We reported earlier that a compact of calcium carbonate (vaterite)/poly(lactic acid) composite (CCPC) was reported to form b-HA on its surface even after 3 hours of soaking in SBF at 37 C. 10) The rapid formation of the b-HA was suggested to originate from the integration of PLA having carboxy groups bonded with Ca 2þ ions for b-HA nucleation and a large amount of calcium carbonate (vaterite) having an ability to effectively increase the supersaturation of b-HA due to the fast dissolution of the nano-sized vaterite. We believe that various novel biomaterials can be prepared using CCPC.…”
Section: Introductionmentioning
confidence: 98%